Improving Energy Efficiency by Using Tree-Based Routing Protocol for Wireless Sensor Network - S, Sathish Kumar; Selvarani, A Grace (International Journal of Computer Sciences and Engineering, 2015)
Wireless Sensor Network (WSN) collects large amount of information and sends them to the Base Station (BS). WSN contains low-cost nodes with limited battery power and battery replacement is not easy for WSN with thousands of physically embedded nodes, which means energy efficient routing protocol should be employed to offer a long-life work time. To achieve this minimizing total energy consumption and balancing WSN load is required. So, in the existing system, a Tree-Based Energy-Balance routing protocol (TBEB) is presented which builds a routing tree using a process where, for each round, BS assigns a root node and broadcasts this selection to all sensor nodes. Subsequently, each node selects its parent by considering only itself and its neighbours information, thus making TEB a dynamic protocol. But in this method the parent node selection is based on only the residual energy level. The drawback in this method is if the parent node has less communication capacity, high interference and congestion there is less network performance in terms of packet delivery ratio, delay, throughput etc. So, an innovative technique is introduced which is named as Tree Based QoS Balanced Routing Protocol (TQR) in order to improve the performance. Communication capacity deals with the data handling capacity of the nodes. The communication capacity is computed based on the utilization factor. For the interference level, the signal to interference noise ratio is computed for computing the interference level of the node. Since congestion significantly reduces the effective bandwidth of a link, the effective link data-rate depends on the congestion level. So, based on this the parent node is selected. An experimental result shows that the proposed system achieves high data rate, throughput and less end-to-end delay.